Sodium Dichloroacetate Pharmacological Effect as Related to Na-K-2Cl Cotransporter Inhibition in Rats - Jūratė Stanevičiūtė; Milda Juknevičienė; Jolita Palubinskienė; Ingrida Balnytė; Angelija Valančiūtė; Rūta Vosyliūtė; Kęstutis Sužiedėlis; Vaiva Lesauskaitė; Donatas Stakišaitis (SAGE Publishing, 2018)
The study objective was to investigate a possible sodium dichloroacetate (DCA) pharmacological mechanism causing an increase in diuresis in rats. The aim was to define characteristics of 24-hour urinary Na + , K + , Cl − , Ca 2+ , and Mg 2+ excretion in Wistar male rats and to evaluate effect of a single-dose DCA and repeated DCA dosage on diuresis. Six control and 6 DCA-treated male rats aged 5 to weeks after a single DCA dose and repeated dosage were tested. The single DCA dose treatment caused a significantly higher 24-hour diuresis when compared to control ( P < .05), and it was related to increased Cl − , Na + , and K + urine excretion and a significant increase in Ca 2+ and Mg 2+ excretion ( P < .05); after the repeated 4-week DCA dosage, the diuresis was not increased, but the excretion of the Na + , Cl − , Ca 2+ , and Mg 2+ ions was significantly higher. Kidney immunohistochemistry has revealed that DCA continuous treatment results in an increase in the size of Henle loop thick ascending limb epithelial cells ( P < .001). The study results show a significantly reduced RNA expression of Na-K-2Cl co-transporter (NKCC1) in thymus of 4-week DCA-treated rats ( P < .03). The study data have indicated a possible mechanism of such pharmacological effect to be NKCC inhibition.